Tracing the Racial History of African American cinema and black narrative control leading to the success of get out (2017) and Black Panther (2018) - Islam, Md. Saiful (Brac University, 2023)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Teaching to Speakers of Other Languages, 2022.